Ab Interno Gel Implant for the Treatment of Glaucoma Patients With or Without Prior Glaucoma Surgery: 1-Year Results. Issue 12 (December 2017) - Hengerer, Fritz H.; Kohnen, Thomas; Mueller, Michael; Conrad-Hengerer, Ina
Abstract : Purpose: The purpose of this study is to evaluate IOP lowering effects and complication management of an ab interno gel implant for the treatment of patients refractory to antiglaucoma medication or glaucoma surgery. Methods: Retrospective analysis of the medical records of 242 consecutive eyes of 146 patients with uncontrolled intraocular pressure (IOP) despite maximum tolerated medical therapy or prior surgical intervention that underwent XEN45 implantation (as sole procedure or in combination with cataract surgery) between March 2014 and June 2015. Data included IOP, number of glaucoma medications, the need for additional surgery, needling, and complications. Results: During the study period, mean IOP had decreased by 54.1% from 32.19 (±9.1) mm Hg to 14.24 (±4.0) mm Hg ( P =0.00; Wilcoxon test). The number of antiglaucoma medications had decreased from a mean of 3.13±1.0 to 0.3±0.7 ( P =0.00; Wilcoxon test). Needling was required between week 1 and months 3 in 27.7% of all eyes to enhance the outflow. Hypotony (IOP<6 mm Hg) was observed in 9 eyes (4.0%) at 1 month but normalized in all eyes at 12 months postoperatively. Two eyes experienced hypotony requiring the refill of the anterior chamber. Conclusions: Our data indicate that the XEN45 gel implant has a favorable safety profile and is an effective treatment option for controlling IOP in glaucoma patients with unregulated IOP despite IOP lowering medical therapy or prior surgical intervention. It offers an effective approach, both as sole procedure and in combination with cataract surgery.